2017
DOI: 10.1016/j.biocontrol.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Supplying high-quality alternative prey in the litter increases control of an above-ground plant pest by a generalist predator

Abstract: Supplying predators with alternative food can have short-term positive effects on prey densities through predator satiation (functional response) and long-term negative effects through increases of predator populations (numerical response). In biological control, alternative food sources for predators are normally supplied on the crop plants; using the litter-inhabiting food web as a source of alternative food for plant-inhabiting predators has received less attention. We investigated the effect of supplying p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 49 publications
0
32
0
4
Order By: Relevance
“…For practical use, the release of the predator could only be efficacious if another prey is available for immature development, or if it is released with the predator. Provision of alternative or complementary food has been done by growers in the release of other groups of predatory mites, especially plant inhabiting phytoseiid predators . Mites of this family have been extensively used for the control of plant inhabiting pests around the world, some species being released preventively, together with the provision of pollen or astigmatid mites …”
Section: Discussionmentioning
confidence: 99%
“…For practical use, the release of the predator could only be efficacious if another prey is available for immature development, or if it is released with the predator. Provision of alternative or complementary food has been done by growers in the release of other groups of predatory mites, especially plant inhabiting phytoseiid predators . Mites of this family have been extensively used for the control of plant inhabiting pests around the world, some species being released preventively, together with the provision of pollen or astigmatid mites …”
Section: Discussionmentioning
confidence: 99%
“…Plants offering non-prey resources to natural enemies may be visited more often by natural enemies than plants that do not supply such resources, and they may thus gain protection from herbivores. Recent research has demonstrated another method for providing alternative prey species in mulch layers, which support the establishment of astigmatic mites and increase densities of soil predatory mites (Grosman et al 2011;Muñoz-C ardenas et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A non-choice performance thrips bioassay was set up using the western flower thrips Frankliniella occidentalis (Pergande). The thrips colony was kept in the laboratory inside cages where bean pods were provided and supplemented with pollen as previously described by Muñoz-Cárdenas et al, (2017). For each plant genotype, 15 leaf discs of 15 mm diameter were made.…”
Section: Methodsmentioning
confidence: 99%